Analysis of Works Dedicated to the Reasons for Revelation - Yakhshilikov Abdulaziz (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article discusses works written on the reasons for the revelation of Qur'anic verses, analyzing the scholarly legacy and research of scholars such as Maymun ibn Mihran, Ali Madini, Ismail Naysaburi, Abulhasan Wahidi, Suyuti, Asqalani, as well as contemporary researchers.